INNOVATIONS INTHE BENEFITS OF MICROSOFT TEAMS IN THE IMPLEMENTATION OF MICROTEACHING ONLINE OPEN UNIVERSITY: INNOVATIONS INTHE BENEFITS OF MICROSOFT TEAMS IN THE IMPLEMENTATION OF MICROTEACHING ONLINE OPEN UNIVERSITY - Dadang Bagus Sancaya Dadang (Jurnal Pendidikan Nusantara, 2022)
Abstract The preparation of this research was based onthe covid-19 pandemic that hit the world. Thisdirectly demands creation and innovation in various sectors of human life, one of which is the world of education. Innovation and creation are a must in the development of the world of education. These learning media have been widely used, especially digital integrated learning media, one of the innovative platforms for use in distance learning is Microsoft Teams. Microsoft Teams is a platform used in S1 PGSD remote lectures at UPBJJ Open University Semarang. This research was conducted on April 2022 – May 2022. The research sample was 73 students of the Elementary School Teacher Education Study Program, UPBJJ Open University Semarang. The results obtained were obtained by 93.15% of students thinking that Microsoft Teams is easily accessible, 54.79% think it is easy to implement, and 43.83% think that Microsoft Teams features are available but need to be updated. The data shows that the majority of students are able to integrate Microsoft Teams into the Integrated Learning (Microteaching) lecture process and are able to elaborate it well. So it is concluded that the use of Microsoft Teams is effective in innovating distance learning.